2008
DOI: 10.1158/1535-7163.mct-08-0519
|View full text |Cite
|
Sign up to set email alerts
|

Psorospermin structural requirements for P-glycoprotein resistance reversal

Abstract: Resistance to chemotherapy reduces its effectiveness, resulting in increased mortality. Psorospermin, a natural product, is a topoisomerase II -directed DNA alkylating agent active against multidrug-resistant (MDR) cell lines, including multiple myeloma. In this study, the mechanism of the P-glycoprotein (P-gp) modulation activity of psorospermin and that of its associated pharmacophore were examined. Flow cytometry shows that doxorubicinresistant multiple myeloma cells (8226/D40) pretreated with psorospermin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…13−18 Recently it was shown that FPh is able to reverse the multidrug resistance in cancer cells and could exert significant chemopreventive activity at least in experimental carcinogenesis. 19,20 A number of statistical and epidemiological studies documented lower cancer rates among psychiatric patients treated with neuroleptic medications, fenothiazines, and among them also treated with FPh. 21,22 It should be mentioned that two phenothiazines, FPh and chlorpromazine (CPZ), together with haloperidol are on the World Health Organization (WHO) list of Essential Medicines of 2009, as three essential drugs in antipsychotic treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13−18 Recently it was shown that FPh is able to reverse the multidrug resistance in cancer cells and could exert significant chemopreventive activity at least in experimental carcinogenesis. 19,20 A number of statistical and epidemiological studies documented lower cancer rates among psychiatric patients treated with neuroleptic medications, fenothiazines, and among them also treated with FPh. 21,22 It should be mentioned that two phenothiazines, FPh and chlorpromazine (CPZ), together with haloperidol are on the World Health Organization (WHO) list of Essential Medicines of 2009, as three essential drugs in antipsychotic treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports from our and other laboratories showed that fluphenazine (FPh), an antipsychotic (neuroleptic) drug from the phenothiazine family, was both a chemosensitizer (MDR modulator, Pgp inhibitor) and a selective inducer of apoptosis in cancer cells or genotoxically damaged cells. Recently it was shown that FPh is able to reverse the multidrug resistance in cancer cells and could exert significant chemopreventive activity at least in experimental carcinogenesis. , A number of statistical and epidemiological studies documented lower cancer rates among psychiatric patients treated with neuroleptic medications, fenothiazines, and among them also treated with FPh. , It should be mentioned that two phenothiazines, FPh and chlorpromazine (CPZ), together with haloperidol are on the World Health Organization (WHO) list of Essential Medicines of 2009, as three essential drugs in antipsychotic treatments …”
Section: Introductionmentioning
confidence: 99%
“…5 However, there are also a few reports of remarkable stereospecificity. 6 Furthermore, the recently published crystal structure of mouse P-gp co-crystallised with the two enantiomeric cyclopeptides QZ59-RRR and QZ59-SSS revealed distinct binding sites for the two enantiomers. QZ59-RRR binds in the center of the P-gp binding pocket, whereas QZ59-SSS binds at two positions: in one position it interacts with hydrophobic residues between TMs 6 and 12, while in the other position it interacts with TMs 8 and 9 and is surrounded by three polar residues.…”
mentioning
confidence: 99%
“…Of all four enantiomers, the naturally occurring (R,R)-enantiomer was the most potent with IC 50 values of 0.072, 0.036, 0.097, and 0.037 µM, respectively, after 96 h of incubation. The pronounced effect against doxorubicin-resistant RPMI8226/D40 cells was further investigated by Carey et al, who found that the retention of doxorubicin was enhanced after pretreatment with psorospermin [ 139 ]. As overexpression of P-glycoprotein is the main reason for doxorubicin-resistance, the authors conclude that the effect is due to mdr1/P-glycoprotein inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…While the latter compound showed low micromolar IC 50 values against RPMI8226 and U266 cells (after only 12 and 8 h of incubation), psorospermin was even inhibiting normal and doxorubicin-resistant RPMI8226 cells with IC 50 values ranging from of 36 to 97 nM (even though the incubation time of 96 h was quite long). Thereby, it was shown that psorospermin was not only acting through the abovementioned P-glycoprotein inhibition but also through topoisomerase II-mediated alkylation by its side chain [ 139 ].…”
Section: Resultsmentioning
confidence: 99%